Influence of some mechanical finishing processes on manufactured leather properties - Ahmed Ibrahim Nasr (Majalah Kulit, Karet, dan Plastik, 2017)
The objective of this study is to investigate the influence of using some mechanical finishing processes on final properties of produced leather types. Nappa, nubuck, pigmented and corrected grain leather types were produced by applying some of the following operations: hang drying, vacuum drying, molissa staking, drum milling, buffing, spraying and/or embossing surface with extreme pressure. Hydrophobic-hydrophilic status, scanning electron micrographs, organoleptic and mechanical properties were determined on all finished leather types. Results showed that water behavior was hydrophobic for nappa leathers, while it was hydrophilic with the rest of produced leather types. Buffing surface in nubuck leather increases the water absorption and water vapor permeability, while the opposite was found when applying external coat layer in pigmented and corrected grain leathers. Applying vacuum drying in nappa leathers increases surface smoothness and surface water contact angle while decreases tensile and tearing strengths. These results elucidate that all studied leather types are suitable for manufacturing purposes except nubuck leather which is not recommended for footwear uppers manufacturing due to its high water absorption. The present study emphasized that while mechanical finishing processes could have profound effects on leathers surface behavior, they must be adequate to the requirements and properties of the end products.